Postnatal depression in mothers bringing infants to the emergency department. Issue 1 (12th November 2012) - Stock, Amanda; Chin, Lynda; Babl, Franz E; Bevan, Catherine A; Donath, Susan; Jordan, Brigid
Abstract : Objective: To determine the prevalence of postnatal depression (PND) in mothers of young infants presenting to the emergency department (ED). Design, setting and participants: Prospective observational study of the prevalence of PND in mothers of infants aged 14 days to 6 months presenting with non-time-critical conditions to the ED of a large tertiary paediatric hospital. Main outcome measures: We assessed PND by applying a self-administered validated screening tool, the Edinburgh Postnatal Depression Scale (EPDS). Mothers of patients were approached before clinician consultation when a social worker was available on site. EPDS scores of 13 and above were considered 'positive'. Univariate analysis was used to determine associations with demographic, maternal and child factors. Results: 236 mothers were approached; 200 consented to participate in the study. Thirty-two mothers screened positively, with a prevalence rate of 16% (95% CI 11.2% to 21.8%). A positive screen was most strongly associated with history of depression (relative risk (RR) 4.8, 95% CI 2.3 to 10.1). Other associations were with single-parent status (RR 2.5, 95% CI 1.1 to 5.4), Indigenous status (4.4, 95% CI 1.8 to 10.4) and 'crying baby' as the presenting problem (RR 2.9, 95% CI 1.4 to 6.2). Fifty-three per cent of mothers had not completed a PND screen before coming to the ED. Conclusions: Mothers of young infants coming to the ED regardless of infant's presenting complaint have a high prevalence of PND determined using the EPDS. Many mothers were not screened for PND before coming to the ED. Clinical staff need to be aware of the condition, incorporate appropriate questioning into the consultation, and refer mothers to support services if necessary.